1996
DOI: 10.1111/j.1460-9568.1996.tb01558.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide/Cyclic GMP Messenger System in Olfactory Pathways of the Locust Brain

Abstract: Nitric oxide is generated by a Ca2+/calmodulin-stimulated nitric oxide synthase and activates soluble guanylyl cyclase. Using NADPH diaphorase (NADPHd) staining as a marker for the enzyme nitric oxide synthase and an antiserum against cGMP, we investigated the cellular organization of nitric oxide donor and target cells in olfactory pathways of the brain of the locust (Schistocerca gregaria). A small subset of neuronal and glial cells expressed cGMP immunoreactivity after incubation of tissue in a nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 37 publications
2
59
2
Order By: Relevance
“…Histochemical studies in honey bees, locusts, and cockroaches have revealed presumable NO synthase activity in some neurons of the antennal lobe (primary olfactory center) and the mushroom body (a higher olfactory and multisensory center) (Müller and Bicker 1994;Bicker 2001;Ott and Elphick 2002), while other neurons in the same centers have been shown to exhibit immunoreactivity to NOinduced cGMP (Bicker et al 1996;Bicker 2001). In honey bees, prolonged activation of PKA in the antennal lobe is implicated in LTM formation (Müller 2000), while in Drosophila, it is thought that the mushroom body is required for LTM formation (Pascual and Preat 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical studies in honey bees, locusts, and cockroaches have revealed presumable NO synthase activity in some neurons of the antennal lobe (primary olfactory center) and the mushroom body (a higher olfactory and multisensory center) (Müller and Bicker 1994;Bicker 2001;Ott and Elphick 2002), while other neurons in the same centers have been shown to exhibit immunoreactivity to NOinduced cGMP (Bicker et al 1996;Bicker 2001). In honey bees, prolonged activation of PKA in the antennal lobe is implicated in LTM formation (Müller 2000), while in Drosophila, it is thought that the mushroom body is required for LTM formation (Pascual and Preat 2001).…”
Section: Discussionmentioning
confidence: 99%
“…If the NADPH-d histochemistry is a marker of NOS-activity as was suggested earlier in both vertebrates [3,21] and invertebrates [1,11] all of the SLABs and a few putative CSCs (tactile and pressure receptors) of earthworms are NOS containing structures. This finding strongly suggests the presence of NO as a neurotransmitter in the earthworms' nervous system and its involvement in the perception of both chemical and mechanical stimuli, moreover in the mediation of sensory information.…”
Section: Discussionmentioning
confidence: 70%
“…Since the above-mentioned primary sensory cells are mechano-and chemoreceptors [16], and neurophysiological experiments proved that both chemo-and mechanoreceptive information entered the CNS via all of the segmental nerves [16], at this stage of our experiments we could only conclude that the putative NOS-expressing fibres mediate both kinds of sensory stimuli. NOS/NADPH-d activity was shown in both chemo-and mechanoreceptors and their central projections in both invertebrates [1,6,11] and vertebrates [7,18,22].…”
Section: Discussionmentioning
confidence: 99%
“…and Newland, 2001), the depression of spiking local interneurons, and the down-regulation of presynaptic inhibition , all by virtue of the patterns of connections they make with these classes of interneurons. It is worth noting, however, that the cGMP staining pattern observed by Aonuma (2002) is not the exception to the rule, because Bicker et al (1996) showed that in the olfactory system of locusts NO also acts on intrinsic interneurons. Clearly there is much still to understand as to where NO is mediating these effects within the terminal ganglion and the precise mechanisms of its action, or indeed where it is acting.…”
Section: No Action In Local Circuitsmentioning
confidence: 93%